Residue, Dissipation Pattern, and Dietary Risk Assessment of Imidacloprid in Chinese Chives - Zhai, Rongqi; Zhang, Kaige; Chen, Ge; Liu, Guangyang; Huang, Xiaodong; Gao, Mingkun; Zhou, Jie; Xu, Xiaomin; Li, Lingyun; Zhang, Yanguo; Wang, Jing; Jin, Maojun; et al. (Frontiers in Nutrition, 2022)
The demand for Chinese chives is growing as they are also rich in vitamins, fiber, and sulfur nutrients. Chinese chives should be sprayed with imidacloprid to control pests and diseases to safeguard their yield and to meet the demands of East Asian consumers for Chinese chives. Overspraying of imidacloprid can lead to residues in Chinese chives, posing a severe risk to human health. To reduce the harmful effects of imidacloprid residues on humans, we investigated the imidacloprid dissipation pattern and the final residue on Chinese chives using the quick, easy, cheap, effective, rugged, and safe (QuEChERS) method combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS). Good linearity (R2= 0.9988), accuracy (expressed as recovery % of 78.34–91.17%), precision [expressed as relative SDs (RSDs) of 0.48–6.43%], and sensitivity [a limit of quantification (LOQ) ≤ 8.07 × 104 mg/kg] were achieved. The dissipation dynamics were consistent with the first-order kinetics, with a half-life of 2.92 days. The final residual levels on Chinese chives were 0.00923–0.166 mg/kg, which is lower than the maximum residue limits (MRLs) of 1 mg/kg for imidacloprid on Chinese chives. A risk assessment index of <1 indicates that Chinese chives are safe for consumption.